Analysis of Hotel Visual Branding and Multimedia Utilization via Instagram Platform: A Case Study of Mercure Hotel Bengkulu - Putri Cempakasari; Gushevinalti Gushevinalti (CV. Media Inti Teknologi, 2026)
Background: The increasing competitiveness of the hospitality industry in the digital era has driven hotels to optimize social media as a strategic communication tool. Instagram, with its strong emphasis on visual branding and multimedia content, plays a crucial role in shaping customer perception, engagement, and brand attractiveness.Aims: This study aims to analyze the visual branding and multimedia utilization strategies implemented by Hotel Mercure Bengkulu through its Instagram platform, focusing on how visual and multimedia elements are integrated to strengthen brand identity and audience engagement.Methods: This research employed a qualitative approach using descriptive content analysis. Data were collected from 90 Instagram posts published by @mercure_bengkulu between January and June 2025, including photos, carousels, and reels. The analysis examined color schemes, composition, content themes, caption styles, and engagement metrics.Results: The findings indicate that Hotel Mercure Bengkulu consistently applies warm color palettes and balanced visual compositions that convey comfort and luxury. Food and beverage content dominates the posts (33.3%) and achieves the highest engagement rate (3.4%). The use of diverse multimedia formats, including photos, carousels, and short videos, effectively increase algorithmic visibility and audience retention.Conclusion: Consistent visual identity and strategic multimedia integration significantly strengthen Hotel Mercure Bengkulu’s digital brand positioning. The results highlight the importance of expanding audience interaction and authenticity through user-generated content. Well-planned multimedia-based visual branding is essential for building engagement and brand loyalty in the hospitality industry.